An update to the definition of zero wave overtopping in floods and reservoir safety. Issue 4 (10th December 2021) - Gillen, Michal; Hewitt, Martin; Brown, Alan
Abstract : EurOtop 2018 includes a definition of zero wave overtopping, related to a non-dimensional value of the measured mean overtopping discharges in laboratory tests. This note summarises the key points and suggests values to be taken as the 'no overtopping' value at the design flood, defined in Chapter 2 of Floods and Reservoir Safety (ICE, 2015).